Endoscopic Mucosal Resection of Mucosal Neoplasm Located on the Duodenal Bulb through Endoscope Retroflexion - Hua LI; Qiang LI; De-jun ZHOU; Jian-zhang HU; Guo-qing ZHANG; Feng-ling LI (Cancer Biology & Medicine, 2010)
OBJECTIVE To assess the results of endoscopic mucosal resection (EMR) of benign mucosal neoplasms located on the duodenal bulb using endoscope retroflexion.METHODS This study involved 14 patients with 16 mucosal neoplasms located on the duodenal bulb. The diameter of each neoplasm was less than 15 mm. After endoscope retroflexion within the duodenum for evaluation of the size, extent and depth of the tumor, EMR was a empted with endoscope retroflexion for removing the lesion in the duodenal bulb. The rate of endoscope retroflexion, the time required for endoscope retrofl exion, median operation time, curative resection rate, enbloc resection rate, complication, and median follow-up period were evaluated.RESULTS Sixteen lesions in 14 patents (median age of 56 years, 5 female, 9 male) were removed through EMR. The mean size of the lesions resected was 6.9 mm (median size of 5.5 mm, range of 3-15 mm). Post-EMR histologic examination revealed Brunner’s gland hyperplasia in 6, gastric mucosal metaplasia in 5, adenoma in 1, chronic inflammation in 3, and benign lymphocytic hyperplasia in 1. The curative resection rate was 100% (16/16), and the enbloc resection rate was 94% (15/16), with EMR. One of the lesions was piecemeal removed through EMR for its large size (15 mm) and for its involving the area from the duodenal bulb to the pyloric ring. The success rate of endoscope retrofl exion within the duodenum was 94% (15/16). The time required for endoscope retroflexion was longer for the fi rst 10 lesions (median time of 2 min, range of 1-2.5 min) than that for the last 5 lesions (median time of 1.5 min, range of 1-2 min). The median follow-up period was 22 months (range of 4-48 months). During the follow-up, no residual, no pyloric or duodenal stenosis was found in any of the patients after EMR. There was no severe hemorrhage, or perforations occurring.CONCLUSION EMR of mucosal neoplasm located on the duodenal bulb through endoscope retrofl exion, which is a feasible and useful adjunctive procedure, appears to be a safe and effective technique.